Penguasaan pelajar sekolah menengah terhadap kata pinjaman Bahasa Arab berasaskan pengetahuan sedia ada - Sapar, A.A.; Salim, N.R.; Husin, A.F.; Pa, M.T. (2013)
This study investigates form four students' level of mastery of the use of Arabic loanwords based on their existing knowledge. Sample of the study involves 150 form four students from three schools of different categories, namely National Religious Secondary School (SMKA), Religious Stream Class (KAA) and Government Assisted Religious School (SABK). This study uses a set of questionnaires and a test on students' mastery level in using Arabic loanwords based on their existing knowledge. Data were collected and analyzed using the Statistical Package for Social Sciences (SPSS version 2.0) to obtain the mean, median and mode. The overall score results showed that the level of mastery of 150 students of Arabic loanwords based on their existing knowledge is high.